Budidaya udang vanname PEMBESARAN UDANG VANNAMEI PADA BERBAGAI SISTEM AKUAKULTUR : TELAAH PUSTAKA - anggi nugraha anggi nugraha; Ayi Yustiati; Yuli Andriani (Journal of Fish Nutrition, 2022)
Vannamei shrimp cultivation has been carried out for quite a long time in Indonesia, the more advanced the era of vannamei shrimp cultivation techniques have developed very rapidly. The main goal of technological developments for vannamei shrimp is a high level of production. The vannamei shrimp culture system with the bioflox method can be interpreted as living organic matter that blends into lumps. The clumps consist of various aquatic microorganisms including bacteria, algae, fungi, protozoa, metazoa, rotifers, nematodes, gastrotricha and other organisms suspended with detritus so that the flocs in shrimp can be used for feed. While the Running water system is the movement of water needed to keep the particles in suspension. If biofloc particles settle, anaerobic slurry pockets often form which can release ammonia or sulfides; sulfide can be directly toxic to animals and can inhibit nitrification, thereby leading to a further increase in toxic nitrogen compounds. For Recirculation Aquaculture system is a shrimp rearing system using the recirculation method without any water change where the wastewater is managed with several filters. The RWS (running water system) system has the advantage that the movement of the water system makes it easier to collect nutrients so they are easy to dispose of and control. The second advantage of the process is that it facilitates nitrification and with a stocking density of 750,000 m2, initial weight of 3.2 grams, final weight of 11.4 grams, daily weight of g/day 0.745, total feed 7450 and survival rate of 85%, food conversion ratio 1.11